Design and locomotion analysis of a novel deformable mobile robot with worm-like, self-crossing and rolling motion. Issue 9 (4th December 2014) - Tian, Yaobin; Yao, Yan-An; Ding, Wan; Xun, Zhiyuan
SUMMARY: This paper presents a novel deformable mobile robot with five degrees of freedom (DOFs). The robot contains two equivalent expandable triangular platforms connected by three equivalent chains. Each platform is a regular triangle with a single DOF. Each chain consists of two links and three joints (one spherical joint at the middle of a chain, and one revolute joint at each end of the chain). Through kinematic and locomotion mode analysis, the robot exhibits three motion modes: worm-like, self-crossing, and rolling modes. The worm-like and self-crossing modes can be used for narrow passages (e.g., pipelines, holes, and caves). The rolling mode has three different directions at the initial state. By switching between these, the robot can operate on rough ground. To verify the locomotion modes and functionality of the robot, the results of a series of experiments performed on a manufactured prototype are reported.